A Critical Analysis of the Sources of Shia Hadith - Achmad Zulham; Apip Suhendra; M. Mighwar; Rizzaldy Satria Wiwaha; Engkos Kosasih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to critically analyze the sources of hadith within the Shia tradition, focusing on major hadith collections such as al-Kafi and Man La Yahduruhu al-Faqih. The methodology of hadith evaluation in the Shia tradition is examined in depth and compared with the Sunni tradition of source criticism. This research employs a qualitative approach using content analysis methods applied to primary and secondary literature related to Shia hadith collections. The findings reveal significant differences in the methodology of hadith criticism between Shia and Sunni traditions, particularly regarding the concepts of ‘adalah (narrator’s integrity), isnad (chain of transmission), and the authority of narration. The Shia tradition places special emphasis on narrations from Ahl al-Bayt and the doctrine of the infallibility of the Imams, which distinguishes it from the Sunni perspective. The study concludes that, despite fundamental methodological differences, both traditions demonstrate scholarly rigor in ensuring the authenticity of hadith as a source of Islamic law, albeit through distinct epistemological approaches.